Endovascular Therapy for Ruptured Cerebral Aneurysms in the Elderly: Poor Accessibility of the Guiding Catheter and Use of Local Anesthesia as the Predictors of Procedure-Related Rupture. Issue 4 (1st October 2015) - Fukuda, Hitoshi; Handa, Akira; Koyanagi, Masaomi; Yoshida, Kazumichi; Lo, Benjamin W. Y.; Yamagata, Sen
Abstract: BACKGROUND: Endovascular therapy is favored for ruptured intracranial aneurysms in the elderly. However, poor accessibility to the aneurysm through the parent artery and use of local anesthesia in this age group may predispose to intraprocedural complications. OBJECTIVE: To evaluate whether age-related poor access to the ruptured target aneurysm and use of local anesthesia are associated with increased incidence of procedure-related rupture during endovascular embolization. METHODS: A total of 117 patients with 117 ruptured aneurysms underwent endovascular embolization at a single institution. Correlation of increasing age with poor accessibility of the guiding catheter was analyzed. In addition, the distance from the aneurysm to the guiding catheter was investigated to identify an association with incidence of procedure-related rupture. Correlation of local anesthesia with procedure-related rupture was also evaluated in the multivariable analysis. RESULTS: Increasing age was significantly associated with poor accessibility of the guiding catheter ( P = .001, Mann-Whitney U test). Procedure-related rupture occurred in 9 of 117 aneurysms (7.7%). Longer distance between distal aneurysms and low-positioned guiding catheters carried a higher risk of procedure-related rupture than a shorter distance between proximal aneurysms and high-positioned guiding catheters (odds ratio, 19.3; 95% confidence interval, 1.84-201; P = .01, multivariable analysis). Use of local anesthesia was also a significant risk factor of procedure-related rupture by multivariable analysis. CONCLUSION: Increasing age was correlated with poor accessibility of the guiding catheter in endovascular embolization of ruptured intracranial aneurysms. Distally located aneurysms treated through a low-positioned guiding catheter and use of local anesthesia increased the risk of procedure-related rupture.